PERAN LEMBAGA PEMBERDAYAAN PEREMPUAN DAN ANAK PINGGIRAN SEROJA MELALUI PUSAT KEGIATAN BELAJAR MASYARAKAT - Vicky Astraedha, Okkydhian; Purwanto, Danang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of PPAP Seroja through the Community Learning Activity Center (PKBM) program in empowering marginalized communities in Surakarta City. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation involving managers, tutors, and learners. The result show that PKBM Seroja functions not only as an educational institution but also as a space for empowerment through three main aspect: equivalency education, personal capacity building, and social interaction. The empowerment process occurs gradually through flexible, participatory, and contextual learning. Based on Zimmerman’s theory, empowerment is reflected in intrapersonal, interactional, and behavioral dimensions, indicated by increased self confidence, communication skills, and real-life actions. Despite challenges such as time constraints and diverse participant backgrounds, institutional support and learner motivation enable the program to run effectively. This study highlights that community-based non-formal education can serve as a strategic approach to enchance the capacity and independence of marginalized communities.